Kebijakan Hukum Perlindungan Konsumen terhadap Kebocoran Data di Platform Fintech - Ayumi Kartika Sari (Cattleya Darmaya Fortuna, 2025)
The development of financial technology (fintech) has brought significant changes to the financial transaction system, but has also increased the risk of leakage of consumers' personal data. Data leaks on fintech platforms can have serious repercussions, including identity theft, misuse of information, and financial loss. This research aims to examine the legal policies that apply in Indonesia to protect consumers from these risks. Using normative juridical methods, this research analyzes main regulations such as Law Number 27 of 2022 concerning Personal Data Protection, Financial Services Authority Regulations (POJK), and Bank Indonesia regulations regarding fintech services. The research results show that even though there are legal instruments governing data protection, implementation and supervision of fintech providers still face various challenges, including weak law enforcement and limited consumer understanding of their rights. Therefore, it is necessary to strengthen policies through harmonization of regulations, increasing consumer digital literacy, and more effective supervision of fintech industry players